MANUAL AND DIGITAL MAKE A MATCH: AN EXPERIMENTAL STUDY ON VOCABULARY AND MOTIVATION - Ni'amah, Lailin; Nur'aini, Siti; Setyaji, Arso (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2025)
Vocabulary mastery is a crucial element of language acquisition, and students' success is significantly influenced by their motivation and the teaching methods used. Traditional approaches often struggle to keep students engaged, which has led to a growing interest in game-based learning strategies. One effective method is "Make a Match," an interactive technique that combines play with educational goals. However, there has been limited research comparing the effectiveness of its manual and digital versions in enhancing vocabulary mastery and learning motivation. This study utilized an experimental design involving two groups of seventh-grade junior high school students. One group received vocabulary instruction through the manual version of Make a Match, while the other group used the digital version. Both groups completed pretests and posttests to assess vocabulary proficiency and filled out a motivation questionnaire. The data were analyzed using descriptive statistics, paired-sample t-tests, and independent-sample t-tests. The findings indicated that both versions of Make a Match significantly improved students' vocabulary acquisition and motivation. The manual version demonstrated slightly higher gains in vocabulary mastery, emphasizing the value of direct peer interaction and face-to-face communication. Meanwhile, the digital version was appreciated for its accessibility and innovative features, despite encountering some minor technical challenges. These results highlight the importance of integrating both traditional and digital approaches in language teaching and provide practical insights for educators seeking to enhance vocabulary learning outcomes.